The aerial invertebrate fauna of subantarctic Macquarie Island. (18th March 2013) - Hawes, Timothy C.; Greenslade, Penelope
Abstract: Aim: The extent and diversity of invertebrate aerial dispersal both on remote islands and in polar regions has long been of interest to biogeographers. We therefore monitored the airborne dispersal of insects and other micro‐ and macroinvertebrates to and on Macquarie Island in order to assess (1) the magnitude and composition of local aerial dispersal activity by the island's invertebrate fauna, and (2) the potential for exotic arrival and establishment. Location: Macquarie Island. Methods: Two robust wind‐traps were run year‐round on Macquarie Island from 1991 to 1994 to collect airborne insects and other micro‐ and macroinvertebrates. Results: More than 3000 invertebrates were caught in these traps over the sampling period in the most comprehensive aerial survey of subantarctic invertebrates to date. Representatives of seven orders of Insecta were captured: Psocoptera, Thysanoptera, Hemiptera, Coleoptera, Diptera, Lepidoptera and Hymenoptera. Other taxa captured included other arthropods (Arachnida and Collembola) but also terrestrial Gastropoda. Evidence of possible long‐distance dispersal (LDD) was limited to two exotic catches (one species of Collembolon, and one species of Thysanoptera). The abundance and composition of indigenous invertebrates caught in the traps indicates that the frequency of short‐distance dispersal (SDD) movements on the island far exceeds that which had previously been realized. Main conclusions: More than half the total catch (53%) was of flightless (i.e. passively dispersed) invertebrates, with 84% of them flightless in one of the two traps. The extent of passive dispersal movements is consistent, with most invertebrates being widely distributed at a whole‐island scale. Aerial dispersal may act as a conduit for non‐indigenous arrivals but this occurs infrequently. Other explanations for exotic species in traps are equally likely. The implications of these findings are discussed in relation to terrestrial invertebrate biogeography.